The mandibular gland secretions and ovarial development of worker honeybees (Apis Mellifera) in the Eastern Cape Province of South Africa - Reece, Sacha Louise (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2001)
The Eastern Cape is an area in which Apis mellifera capensis, A. m. scutellata and their hybrid are known to naturally occur. I investigated the mandibular gland profiles and ovarial development of queenright workers from 4 localities. Their queens were then removed to determine how these aspects changed upon queen loss. In addition, drifted bees were analysed in the same way to determine how these factors changed once they had gained entry to a foreign hive. The queenright bees, form all 4 localities were found to have 9HDA as the most abundant of the 5 fatty acids measured and all localities had small percentages of 9ODA in their mandibular gland secretions. This resulted in relatively high queenright 9ODA:10HDA and 9HDA:10HDAA ratios. Despite this the percentage of bees with undeveloped ovaries was consistent with their queenright status. The mean values of these 2 ratios were significantly higher in the bees from East London and Cradock than those from Port Elizabeth. Steynsburg's bees were intermediate in this regard. Upon queen loss, the bees from all 4 localities had an increase in the percentage of 9ODA but the other compound changes in varying ways. East London's bees were the only ones not to become significantly more queen-like after queen loss. After 14 days without a queen, the mean values of these 2 ratios were much higher in the bees from Port Elizabeth than those from the other localities. Certain individuals from Port Elizabeth had values of these ratios that exceeded those found in A. m. capensis queens. Port Elizabeth was the only locality to display any surrogate queens and exhibited the highest increase in the number of bees with partially or fully developed ovaries. While certain individuals from the other localities had values of these ratios that exceeded these values reported in A. m. scutellata queens, Steynsburg's bees were the only ones that did increase in in terms of the number of bees with developed ovaries subsequent. The bees from Steynsburg were shown to suppress the mandibular gland and ovarial development of drifters from Port Elizabeth while bees from East London did not.
Keywords: Honeybee -- South Africa -- Eastern Cape; Honeybee -- Behavior; Honeybee -- Physiology